A comparison of age-standardised event rates for acute and chronic coronary heart disease in metropolitan and regional/remote Victoria: a retrospective cohort study. (December 2016) - Xanthos, Paul; Gordon, Brett; Begg, Stephen; Nadurata, Voltaire; Kingsley, Michael
Abstract Background Acute and chronic coronary heart disease (CHD) pose different burdens on health-care services and require different prevention and treatment strategies. Trends in acute and chronic CHD event rates can guide service implementation. This study evaluated changes in acute and chronic CHD event rates in metropolitan and regional/remote Victoria. Methods Victorian hospital admitted episodes with a principal diagnosis of acute CHD or chronic CHD were identified from 2005 to 2012. Acute and chronic CHD age-standardised event rates were calculated in metropolitan and regional/remote Victoria. Poisson log-link linear regression was used to estimate annual change in acute and chronic CHD event rates. Results Acute CHD age-standardised event rates decreased annually by 2.9 % (95 % CI, −4.3 to −1.4 %) in metropolitan Victoria and 1.7 % (95 % CI, −3.2 to −0.1 %) in regional/remote Victoria. In comparison, chronic CHD age-standardised event rates increased annually by 4.8 % (95 % CI, +3.0 to +6.5 %) in metropolitan Victoria and 3.1 % (95 % CI, +1.3 to +4.9 %) in regional/remote Victoria. On average, age-standardised event rates for regional/remote Victoria were 30.3 % (95 % CI, 23.5 to 37.2 %) higher for acute CHD and 55.3 % (95 % CI, 47.1 to 63.5 %) higher for chronic CHD compared to metropolitan Victoria from 2005 to 2012. Conclusion Annual decreases in acute CHD age-standardised event rates might reflect improvements in primary prevention, while annual increases in chronic CHD age-standardised event rates suggest a need to improve secondary prevention strategies. Consistently higher acute and chronic CHD age-standardised event rates were evident in regional/remote Victoria compared to metropolitan Victoria from 2005 to 2012.